Modeling Individual Defiance of COVID-19 Pandemic Mitigation Strategies: Insights From the Expanded Model of Deterrence and Protection Motivation Theory - Burruss, George W. (Criminal justice and behavior, 2021)
The governmental responses to the COVID-19 pandemic include concerns for both public health and formal social control. Government leaders asked the public to help mitigate the spread of the virus by adopting various protective behaviors. Our purpose was to evaluate and explain defiance of COVID-19 mitigation strategies, drawing from the expanded model of deterrence and protection motivation theory. A national sample of 600 American adults were surveyed about perceptions of, and behaviors during, the early part of the COVID-19 pandemic, including defiance of COVID-19 mitigation strategies. Perceived severity of the disease, certainty about dying from it, and how much control one has over getting it each predicted fear of COVID-19. Defiance of COVID-19 mitigation guidelines appear to be a combination of rational choice considerations and emotions. Government and health officials should consider how the public evaluates messages about taking protective actions to maximize compliance.